Data-Driven Impedance Matching in Multilateral Teleoperation Systems - Mohd Syakirin Ramli; Hamzah Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper addresses a tuning approach to improve transparency between master and slave manipulators in a multilateral teleoperation system. The slave manipulators comprised of multi-agents of simple mass are converted into a bilateral system through the passive decomposition technique. There are two main operations being considered, namely; grasping and handling. The object grasping is achieved through consensus control. For handling, an equalizer constructed by a Laguerre function connected in-feedback-loop to the master manipulator is chosen and tuned to achieve impedance matching between both sides of teleoperation. Fictitious Reference Iterative Tuning (FRIT) is adopted to properly tune the selected equalizer. The result shows that by introducing an optimally tuned equalizer, the overall impedance matching and transparency between the single master and multi-slave manipulators are improved. Finally, the effectiveness of the proposed tuning algorithm is presented through a numerical example.